Franz Kafka's relation to Judaism - Oppenheimer, A (1977)
Excerpt from introduction: This thesis aims to examine Kafka's life and work in relation to what is arguably the crucial factor in his complex historical, cultural, literary and religious background. The particular relevance of his Jewishness is a subject that has occasionally been discussed in the study of Kafka; attention has been drawn to it especially by his Jewish contemporaries and friends, but the issues involved in it have not yet received exhaustive investigation. The main part of my thesis is devoted to the subject of Kafka's interest in Jewish mysticism, notably in its Hasidic form, in the later years of his life. It shows how his search to regain a sense of participation in Jewish tradition, combined with religious impulses deeply inclined towards an esoteric spirituality, led him to practise his art in the light of this interest as a religious pursuit with unmistakably mystical intent. What I hope becomes clear from my work is the course of individual development by which growing concern for his relation to Jewish tradition led Kafka to deeper appreciation of his historical situation, and guided his increasing sense of moral and spiritual commitment to his time, despite (or because of?) the deficiencies he perceived in it, in a 'task' undertaken through the medium of his art. In selecting nine stories from the Landarzt collection for commentary in the final chapter, I have chosen to concentrate on a crucial period in Kafka's literary development that began in 1916/17, when his continuing, earnest assessment of his position as a Jew had an evidence influence upon his choice of narrative subject and technique. The stories have been considered not in the published sequence of the Landarzt collection, but in an order that seems appropriate to discussion of various aspects of their Jewish context. Where possible, my commentaries upon these stories are related to themes previously identified in discussion of the Oktavhefte, which were begun soon after the collection was completed and contain the chief evidence of Kafka's growing mystical pre-occupation.